Islamization in translation and transition - Isahak, Aldila (2015)
This paper expounds the concept of Islamization. Islamization of contemporary human knowledge is based on two premises: contemporary human knowledge is Westernised and secularized, and Islam brings true knowledge. Therefore, contemporary human knowledge should be based on Islam, and this can only be done through Islamization. In translating the ideologies that are foreign to Islam which at the same time are dominant ideologies practised and adopted by some Muslims as their ways of life, Islamization acts as the remedial filtration; it is a means and a process. This remedial filtration has two functions; filtration of elements that contradicts the concept of tawhid and the religion of Islam, thereby isolating the alien, harmful and foreign elements to Islam. The second function is the application of the remedy that is found in Islam and the concept of tawhid after the cause as well as the harmful elements to Islam have been isolated in those ideologies. Hence, the role of Islamization in translating foreign ideologies also marks a transition to making a worldview that is based on tawhid. An example of the teaching of Political Thought I & II at the Department of Political Science, of Kulliyyah Islamic Revealed Knowledge is taken as a case study in this exposition.